From Emissions to Economy: Company Characteristics and Carbon Disclosure in Southeast Asia - Warokka, Ari; Barroso, Manuel Monjas; Aqmar, Aina Zatil (Journal of Sustainable Economics, 2024)
This study investigates the relationship between company characteristics, carbon emission disclosure, and economic consequences in five ASEAN countries. By utilizing data from 2008 to 2017, the research focuses on non-financial companies, selected due to their prominence as the highest carbon-emitting nations in the ASEAN region. Results reveal that profitability positively influences carbon emission disclosure, while leverage exhibits no significant effect. Additionally, company size positively impacts carbon emission disclosure, whereas sales growth demonstrates a negative effect. Furthermore, carbon emission disclosure positively affects economic consequence variables. These findings offer practical implications for practitioners and investors, emphasizing the importance of considering carbon emission disclosure in investment decisions.